1995
DOI: 10.1074/jbc.270.34.19949
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Persistent Desensitization of m3 Muscarinic Acetylcholine Receptor-stimulated Phospholipase D

Abstract: Activation of muscarinic acetylcholine receptors (mAChR) in human embryonic kidney (HEK) cells stably expressing the human m3 subtype leads to stimulation of both phospholipase C (PLC) and D (PLD). mAChR-stimulated PLD was turned off after 2 min of receptor activation with either the full (carbachol) or partial agonist (pilocarpine) and remained completely suppressed for at least 4 h. Partial recovery was observed 24 h after agonist removal. This rapid arrest of PLD response was not due to a loss of cell surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 32 publications
1
31
1
Order By: Relevance
“…On the other hand, it was found that the recovery period for the thrombin receptor is 1 h in endothelial cells, but 16 -18 h in megacaryoblastic cell lines (45). The m3-cholinergic receptor transfected in HEK 293 cells remained fully desensitized at 4 h and only partially desensitized 24 h after a short carbachol treatment (2 min) (46).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was found that the recovery period for the thrombin receptor is 1 h in endothelial cells, but 16 -18 h in megacaryoblastic cell lines (45). The m3-cholinergic receptor transfected in HEK 293 cells remained fully desensitized at 4 h and only partially desensitized 24 h after a short carbachol treatment (2 min) (46).…”
Section: Discussionmentioning
confidence: 99%
“…This desensitization is apparently not a result of the loss of cell-surface receptors, but reflects a rapid and sustained uncoupling of the receptors from the activation of PLD. Second, it has been shown that addition of the phorbol ester PMA induces a pronounced stimulation of PLD activity in m3-HEK cells (40,41) as well as in many other mammalian cells (42,43). Examination of the published data indicate that 0.1 M PMA increased PLD activity to levels ϳ4-fold higher than those seen with a maximal concentration of carbachol (40).…”
Section: Arachidonate-mediated Ca 2ϩ Entry In Hek293 Cellsmentioning
confidence: 97%
“…However, several characteristics of this response in the m3-mAChR-transfected HEK293 cells indicate that this is unlikely to be the basis for the observed carbachol-induced increase in arachidonic acid generation. First, the activation of PLD by the m3-mAChR stably transfected into HEK293 cells has been shown to completely desensitize within 2 min of stimulation, even at the low concentrations of agonist used in this study (40). This desensitization is apparently not a result of the loss of cell-surface receptors, but reflects a rapid and sustained uncoupling of the receptors from the activation of PLD.…”
Section: Arachidonate-mediated Ca 2ϩ Entry In Hek293 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In human embryonal kidney cells, muscarinic activation of PLD ceased after 2 mm due to desensitization (Schmidt et al, 1995). Thus, it was conceivable that CCh-induced PLD activation was desensitized rapidly in PC12 cells.…”
Section: Pld Activation and Ca 2~-dependent Tyr Phosphorylation 423mentioning
confidence: 99%